Os prescritos & as ações de inclusão na sala de aula regular - Rodrigues, Ana Maria de Oliveira (2009)
This work considers a study of as they are being interpreted the inclusion prescribed ones and as they are being managed in the activity of works of professionals who act with pupils with necessity educational special - NEE. The objects used in this take over on a contract basis are clippings of lapsings contained in national laws in such a way as international that they regulate this subject, as well as writings in audio and video of lessons given for two teachers of different areas (arts and sciences) that they work with the same group of nineteen pupils, being that it has between them a pupil with syndrome of Down, beyond being used three interviews with the teachers and others two on people the pedagogical area of the school. The analysis if return for the frequency with that the agents use the daily lapsings in its practical being that to direct the work for this end, I adopted slight knowledge of prescribed work and carried through work (Schwartz, 1998; 2000; 2002; Nourodine 2002) as well as I used estimated of Amigues (2003; 2004) to investigate the real activity of the teaching work. Some devices if had shown excellent for concretion of this study such as: interdiscurso, the cenografia and the ethos which are inserted concepts in the field of the language (Maingueneau, 1998 2005; 2007) this last one, related ace interviews, allow to analyze what the citizen says and the way as it says. The research made possible to verify that the practical one of the adopted actions, most of the time an involuntary act that generally occurs with the question of the inclusion, nor always condiz with the lapsing due to one strong presence of instituted knowing that it is internalizado from the teaching experience